Gender Equality in the Al-Qur'an Surah An-Nisa Verse 34 (Comparative Study of Quraish Sihab and Ibn Asyur) - Nasrullah, Muhamad; Halimatussa'diyah; Rahman, Pathur; Hakim, Lukman Nul (Adabuna : Jurnal Pemikiran dan Pendidikan, 2024)
This research discusses gender equality in the Qur'an surah an-nisa verse 34. Gender is the result of social and cultural constructions that regulate relationships between men and women. Discussions about gender are triggered by the fact that most of society is still influenced by patriarchal culture. For example, verse 34 of surah an-Nisa' in the Qur'an emphasizes that the advantages possessed by men are considered a gift given by Allah to support their role as husbands and family leaders. In this research, the author emphasizes gender analysis and connects it with the concept of equality between men and women, using descriptive-analytical methods. The objectives of this research are 1) To find out how gender is in the interpretation of Quraish Sihab and Ibn Asyur. 2). This research is Library Research, this research uses a comparative approach. Data collection techniques: 1) Collect and search for references relevant to the research object. 2) Classify books based on type (primary and secondary). 3) Selecting data, namely selecting and retrieving data related to research. 4) Verify and confirm data with other sources to ensure its validity. 5) Interpret the data that has been collected. The results of this research are that men are considered superior to women because they provide a dowry and support, have more physical strength and intelligence.